Cronologia de erupção dentária decídua em quatro coortes de nascimento brasileiras (BRISA) - MARTINS, Rafiza Felix Marão (2019)
Introduction: Logan's (1935) "human deciduous tooth eruption chronology" table, modified by McCall and Schour (1949), has long been accepted worldwide as a standard, although its results are based on an inaccurate methodology as well as evaluation of children from regions with a high level of socioeconomic development. Deciduous tooth eruption is a phenomenon that follows a chronological rhythm and can be influenced by some environmental factors besides genetic ones. Among them, it is possible that preterm birth (PTB) is related to the delay in eruption chronology. Objectives: To develop a reference curve for deciduous tooth eruption as well as to evaluate the effect of preterm birth on deciduous tooth eruption chronology. Methods: In the first article, a sample of 3,733 children, aged 12 to 36 months, from the four cohorts that make up the BRISA was used. The study design was cross-sectional. A reference curve was drawn with the number of erupted teeth by age using the Generalized Additive Models for Location, Scale, and Shape (GAMLSS) method. The explanatory variable was the corrected child's age and the dependent variable was the number of erupted teeth. In the second article, a longitudinal study was conducted in the city of São Luís-MA, with 1,769 children evaluated at birth and in the second year of life. Exposure variables were gender, economic class, skin color, corrected or chronological age and PTB. The outcome was chronology, assessed by the number of deciduous teeth erupted at T2. The association between PTB and the number of erupted teeth was evaluated by a negative binomial regression with hierarchical analysis. Results: According to the elaborated reference curve, at 12 months of age, 25% of children had four or less erupted teeth, while 75% had seven or fewer. At 24 months of age, 5% had less than 12 teeth, while 75% had 18 or more. At 36 months, about 50% of the study population had complete deciduous dentition (20 teeth). In the analysis with chronological age, older age and brown skin color were associated with the largest number of erupted teeth, while PTB was associated with the smaller number. When the age of the children was corrected, preterm birth did not remain associated with the number of erupted teeth. Conclusions: An advantage of using a reference curve for the number of erupted teeth by age is that this sophisticated statistical method can describe the developmental evolution of a child with comparative patterns, assists pediatric care, estimates children's ages, assesses of somatic growth and development, and identify a sign of adjacent pathologies. There was no association between sex and eruption chronology. The association between PTB and delayed eruption chronology seems to be related only to the age of children, and not necessarily to PTB.